Wind as a sustainable alternative energy source in Malaysia - a review - Didane, Djamal Hissein; Ab Wahab, Abas; Shamsudin, Syariful Syafiq; Rosly, Nurhayati (Asian Research Publishing Network (ARPN), 2016)
Wind energy is being considered all over the world due to the clean characteristics that it possesses and prevalent virtually everywhere in the world. With the current existing technology, a wind turbine could only harness a small portion of energy from the available wind. The amount of harnessed energy could be significantly decreased, if proper wind energy assessments (i.e. micrositing, geographical condition, wind regime characteristics, etc.) were not performed carefully and effectively. As previous studies have shown that, most of the projects which seem to be unfeasible were due to environmental problems such as appropriate site selection, and not technological problems such as wind turbine design. This study presents and discusses the main factors to be considered when undertaking wind energy project in any potential site, so that significant amount of energy could be harvested.